In Ukraine or on Ukraine: the Great Russian chauvinism from the linguistic perspective - Fedorenko, Lesia (Current issues of Ukrainian linguistics: theory and practice, 2023)
This article is determined to analyze the way Russian political and ideological system is using linguistics in the means of its informational and psychological aggression against Ukraine. The war launched by Russian Federation has become the culmination of its prolonged aggressive actions on many fronts: ideological, economical, cultural, linguistic and so on. Current cremlin hosts are trying to regain full control over Ukraine in every imaginable way, drawing on the previous political regimes' experience. This article investigates one of the definitions of chauvinism as harassment of so-called "small nations" on the domestic and international levels that is shaping into political oppression and assimilation of languages. Have it that cremlin ideologues have always exploited any opportunity to diminish Ukrainians' self-consciousness, in particular by means of different quasi-scientific theories. Here we explored one example of the forementioned such as the creation of fake exception to the rule of spelling of prepositions "in" and "on" with administrative geographical names by Russian philologers that only applied to place-name "Ukraine". In contradiction to linguistic norms of Russian language Russians use "on Ukraine" in accusative and locative cases. We respectively analyzed arguments of Soviet linguists D. Rozental and K. Bilinskyy, and also modern Russian geographers and their theory of geo concept that basically comes to one statement: such version has been made up through history and is backed up by the expression "on the outskirts". The Ukrainian linguist I. Ohiyenko's work, in which he explained that the expression "in Ukraine" positioned it as a separate state, is mentioned in the article. After the collapse of the Soviet Union the logical norm "in Ukraine" was being used in the official documents of Russian Federation for a while, but after the cremlin tacked its course to re-establish its dominance over the former Soviet republics, they returned to the previous version. The sources that have been studied in the article point out that the political and ideological system is of a paramount importance for Russian linguistic science and is using it as a non-lethal weapon against Ukraine.
Keywords: assimilation of language, linguicide, self-consciousness, national identity, place-name, conceptual world view, informational andpsychological aggression.